Chemical Composition and Antibacterial Activity of the Essential Oil from Tagetes erecta L. Grown in Northeastern Brazil - , Márcia Maria Mendes Marques, Antonio Carlos Nogueira Sobrinho, Selene Maia de Morais, Raquel Oliveira dos Santos Fontenelle, Maria Izabel Florindo Guedes (Archives of Current Research International, 2025)
Aims: Faced with the increase in microbial infections linked to the phenomenon of drug resistance, research with natural products is promising. Tagetes erecta L., known as "cravo-de-defunto" in Brazil, is an ornamental plant used in folk medicine as an antimicrobial and to treat skin infections, fever, and digestive disorders. This study aimed to describe the chemical composition and report the antimicrobial activity of T. erecta. Study Design: The medicinal plant was collected in the state of Ceará, Brazil, followed by extraction of the essential oil, using the hydrodistillation method. This study was analyzed by gas chromatography/mass spectroscopy to the essential oil. In addition, agar-well diffusion, and broth microdilution methods to the antimicrobial assays. Place and Duration of Study: Ceara State University, Fortaleza, Brazil, between 2016 and 2018. Methodology: T. erecta essential oil was obtained by hydro-distillation in a modified Clevenger type apparatus and analyzed by gas chromatography/mass spectroscopy. The antimicrobial activity was performed by agar-well diffusion and broth microdilution methods. The minimum inhibitory concentration (MIC) was determined against strains of Gram-positive and negative bacteria. Results: Fourteen components, representing 87.99% of the oil, were identified. Monoterpenoid ketones represented the main fraction with piperitone (45.72 %) as the major constituent. The agar well-in method using EO exhibited high activity against E. faecalis, S. aureus, S. epidermitis, S. pyogenes, E. coli and P. mirabilis. EO from T. erecta was more active against Gram positive than Gram negative bacteria. Conclusion: The essential oil of T. erecta showed strong antibacterial activity against important human pathogenic Gram positive and Gram-negative bacteria probably due to the antibacterial compound piperitone, which is present in high yield, nevertheless synergism could occur with other minor active constituents. In silico molecular docking studies are needed to investigate possible pharmacological mechanisms of action.